Us, them, and the war on terror: reassessing George W. Bush's rhetorical legacy. Issue 1 (2nd January 2017) - Lee, Michael J.
ABSTRACT: In this essay, I try to answer a few basic questions about George W. Bush's war rhetoric: (1) How did the president talk about the Iraqi people specifically and Arabs and Muslims generally? (2) How did that vision of Iraqis, Arabs, and Muslims shape the war and its aftermath? Bush did not talk about tyrants and terrorists the same way he did everyday Arabs and Muslims. Tracking the simplified, singular vision of a democratic, freedom-loving Arab and Muslim Other that the Bush administration anticipated, based policy around, and, in the end, failed to find is vital to account for the failures of the war on terror and to differentiate Bush's imperialism from fin de siècle imperialists, Orientalists, and garden-variety racists before and after his presidency. The Bush administration went to both war and postwar on the basis of a deeply flawed constitutive framework, but where Arabs and Muslims were concerned, that framework failed because of presumed sameness, not difference. Put differently, calamities in war on terror were due to violence done to those construed as savages and violence enabled by a total failure to strategize around difference.